Genomics and animal production - Ponce de León, F. Abel (2020)
Developing countries have the challenge of achieving food security in a world context that is affected by climate change and global population growth. Molecular Genetics and genomics are proposed as technologies that will help to achieve sustainable food security. Technologies that have been developed in the last decade such as the development of genetic markers, genetic maps, genomic selection, next-generation sequencing, and DNA editing systems are discussed. Examples of some discoveries and achievements are provided.